Antioxidant capacity, phytochemical profiles, and phenolic metabolomics of selected edible seeds and their sprouts - Liu, Hong-Yan; Liu, Yi; Li, Ming-Yue; Ge, Ying-Ying; Geng, Fang; He, Xiao-Qin; Xia, Yu; Guo, Bo-Li; Gan, Ren-You (Frontiers in Nutrition, 2022)
Sprouts are recognized as nutritional and functional vegetables. In this study, 17 selected seeds were germinated simultaneously. The antioxidant capacity and total phenolic content (TPC) were determined for sprouts among different species and germinated days. Both seed and sprout of white radish, with the highest antioxidant capacity and TPC among species, were further determined for phenolic metabolomics. Four phenolic classes with 316 phenolic metabolites were identified. 198 significantly different metabolites with 146 up-regulated and 52 down-regulated were confirmed, and high amounts of phenolic acids and flavonoids were accumulated in the sprout. Six metabolic pathways, including phenylpropanoid biosynthesis, phenylalanine metabolism, biosynthesis of various secondary metabolites, biosynthesis of secondary metabolites, metabolic pathways, and flavone and flavonol biosynthesis, were significantly activated. Significant correlations were found between the antioxidant activity and TPC/phenolic profiles. Therefore, sprouts are more nutritious than seeds and can be a good source of dietary polyphenols, especially white radish sprouts.